Strengthening the Institutional Setting for Regulatory Reform The Experience from OECD Countries - Cordova-Novion, Cesar (OECD Publishing, 2011)
This Working Paper analyses the institutional setting for regulatory reform. It is the first comprehensive analysis of regulatory oversight bodies. The analysis adopts a functional approach through four core functions: i) oversight of the rule-making process; ii) assisting rule makers in their evidence-based analysis; iii) challenging the quality of regulatory proposals; iv) advocating for quality/better regulation. The report analyses the key factors contributing to success, as well as elements for the credibility of regulatory oversight. The report also finds that regulatory quality oversight represents a tool for policy coherence for countries and needs to be articulated with other core policies, such as microeconomic and competition-oriented reforms, as well as overall reforms of the public administration. Forging of a political constituency requires active communications, political buy-in and support from a champion, and an external constituency of interested parties to support advocacy. The report concludes with a possible checklist for policy makers interested in consolidating regulatory oversight in their respective national settings
Keywords: Governance